Numerical and Experimental Investigation of Wind Load on Photovoltaic Panel Assemblies - Ol’ga Hubová; Michal Franek; Marek Macák (Current Approaches in Science and Technology Research Vol. 4, 2021)
The chapter presents the aerodynamic study of solar panel assemblies and the determination of wind load. In the first part, the task is solved by computer simulation of the wind flow around the proposed rectangular assembly in the scale of 1:1 using the FLUENT ANSYS program and realization of experimental measurements in the wind tunnel with a boundary layer (BLWT) in Bratislava is presented subsequently. The aim of the solution was to determine the maximum pressure and suction wind load on top and bottom surfaces of panels. The resulting net pressure coefficient represents the maximum local pressure in each panel row as maximum values from all wind directions. The experimentally obtained net pressure coefficient values were compared with computer simulation and the procedures mentioned in standard STN EN 1991-1-4. It can be seen that the inner panels are loaded considerably less than the standard defines. The panels placed on the side of the assembly or on the edge of the aisle are loaded significantly more than the standard defines. Frontal panels are also less wind stressed than in the standard defines.